Audiological Patterns in Patients with Autoimmune Hearing Loss - Psillas, George K.; Dimas, Grigorios G; Daniilidis, Michalis; Binos, Paris; Tegos, Thomas; Constantinidis, Jiannis (My University, 2021)
Introduction: The aim of this study was to illustrate clinical and audiological patterns of hearing impairment in patients with autoimmune hearing loss (AIHL). Methods: Fifty-three patients with AIHL were retrospectively recruited, and a tapering schema of steroid treatment was administered in all these patients. The diagnosis of AIHL was essentially based on clinical symptoms, such as recurrent, sudden (sensorineural hearing loss [SSHL]), fluctuating, or quickly progressing (<12 months) SSHL (uni-/bilateral), in association with the coexistence of autoimmune diseases, high antinuclear antibodies (ANA) and the presence of human leukocyte antigen (HLA) B27, B35, B51, C04, and C07. Logistic regression analysis was applied to correlate the clinical data and laboratory features of AIHL with final outcomes. Results: The onset of AIHL was mainly progressive (49%), followed by SSHL (39.6%) or fluctuating (11.3%). The pure-tone audiogram showed more commonly a downsloping pattern (42.6% of ears), but also an upsloping, flat, cookie-bite, or inverse cookie-bite shape. Bilateral progressive AIHL was more frequently simultaneous (23 patients) than heterochronous (4 patients). Nineteen patients (35.8%) showed a favorable response to steroid therapy. The presence of recurrent, bilateral SSHL versus recurrent, unilateral SSHL had statistically negative effect on hearing recovery (OR = 0.042, p < 0.05). The heterochronous bilateral SSHL may have better prognosis than simultaneous bilateral SSHL (OR = 10.000, p = 0.099). The gender, age, concomitant autoimmune disease, high ANA, HLA alleles, tinnitus, and vestibular symptoms had no statistical effect on a favorable outcome of AIHL. Conclusions: A bilateral, simultaneous, and progressive hearing loss combined with downsloping audiogram occurred more often in patients with AIHL. Bilateral simultaneous SSHL with recurrences represents the worse prognostic form of AIHL.
Keywords: Autoimmune disease; Inner ear; Hearing loss; Tone audiometry; Human leukocyte antigen; Fluctuating hearing